2019
DOI: 10.1002/jsfa.9579
|View full text |Cite
|
Sign up to set email alerts
|

Quantity assessment of polyphenols, glycoalkaloids and saponins in Solanum scabrum berries of different genetic sources and maturity by HPLC/UV–visible/MS methods

Abstract: BACKGROUND Solanum scabrum berries in sub‐Saharan Africa are prolific but neglected as an agricultural resource. Recognition and application of such underutilized resources rely on systematic study of the relevant phytochemicals of commercial value. RESULTS The quantities of a total of 54 phytochemicals in Solanum scabrum berries were assessed using HPLC‐MS methods. Berries from eight different genetic sources were analyzed with two entries monitored across different maturation stages. There was a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Glycoalkaloid concentration is low in matured berries. Solanum scabrum mature berries contain up to 1500 mg of glycoalkaloids (Yuan et al., 2019). Such a high concentration of glycoalkaloids in berries could be essential for medicinal purposes (Al‐Ashaal, 2019).…”
Section: Antinutritional Factors Of Ansmentioning
confidence: 99%
“…Glycoalkaloid concentration is low in matured berries. Solanum scabrum mature berries contain up to 1500 mg of glycoalkaloids (Yuan et al., 2019). Such a high concentration of glycoalkaloids in berries could be essential for medicinal purposes (Al‐Ashaal, 2019).…”
Section: Antinutritional Factors Of Ansmentioning
confidence: 99%
“…Solasodine and its glycosides were detected in the selected aqueous extracts, S. linnaeanum root extract (Sl R) and Ss F , which have been shown to have nematicidal activity. The identification of these spirostane-type alkaloids was based on ions at m/z 415 (protonated molecule) and at m/z 253, 271 and 157 in MS2 and/or MS3 according to Yuan et al (2019) [ 42 ]. Therefore, in Ss F extract the solasodine and its glycoside solamargine were detected and their identification was confirmed by authentic standards.…”
Section: Resultsmentioning
confidence: 99%
“…Berries of two S. scabrum accessions, Ex Hai and BG 29 from the World Vegetable Center (WorldVeg, Arusha, Tanzania) and two S. nigrum accessions, one from a private seed company (Simlaw Seeds, Nairobi, Kenya) and the other (PI 381289) from the United States Department of Agriculture (USDA, Ames, IA, USA), were analyzed in this work. The samples originated from the same field trial as reported in the prior work 7,8 …”
Section: Methodsmentioning
confidence: 99%
“…In our recent study, the phytochemicals in SNBs were profiled using ion trap mass spectrometry (MS), revealing a wide range of toxic glycoalkaloids in SNBs, as illustrated in Figure 1 7 . The contents of glycoalkaloids were found to present as large as three orders of magnitude divergence across varied genetic lines, rendering SNBs deficient in glycoalkaloids safe for consumption while those high in glycoalkaloids toxic to consume 8 (also see Table S1, supporting information, for phytochemical profile in S. nigrum berries). As such, in places where SNBs are considered edible, it is of importance to understand the glycoalkaloid content and have a robust system of analysis and toxicity inspection, especially for those genetic lines and sources of materials originating from the wild harvest and/or landraces cultivated for production and marketing which have not yet been screened to ensure consumption safety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation